SYNTHESIS AND ANTIOXIDANT ACTIVITY OF NOVEL 2-ARYL SUBSTITUTED BENZOTHIAZOLE DERIVATIVES - Likhar, Rupali; Perumal, P.; Kolhe, Nitin; Bhaskar, V. H.; Daroi, Pratibha (International Journal of Current Pharmaceutical Research, 2015)
Objective: A series of 2-aryl substituted benzothiazole was designed and synthesized with various substituted benzoic acid. 2-mercaptobenzothiazole and thionyl chloride also used to get carbothiaote. The present study was carried to assess the pharmacological potential towards antioxidant activity of 2-aryl substituted benzothiazole derivatives. Methods: The antioxidant activity of the synthesized compounds was evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH), and superoxide radical scavenging assay methods. Results: Compounds showed significant radical scavenging potential due to the presence of electron donating substituent. Conclusion: These indicate that benzothiazole derivatives showed the defence mechanism to prevent formation of excess free radicals.